Effect of acupuncture on cognitive impairment induced by sleep deprivation in animal models: a preclinical systematic review and meta-analysis - Liu, Chang; Su, Yutong; Yau, Yuen-ming; Lin, Huize; Chen, Yihao; Fang, Weijian; Xu, Nenggui; Wu, Zhennan (Frontiers in aging neuroscience, 2025)
Sleep deprivation (SD) has been associated with cognitive deficits, mediated by mechanisms such as neuroinflammation and oxidative stress. Acupuncture, a core component of traditional Chinese medicine, has shown promise in mitigating SD-induced cognitive impairment. However, the effectiveness and underlying mechanisms of acupuncture need further validation through high-quality evidence. This study aims to evaluate the therapeutic effects and molecular mechanisms of acupuncture on cognitive impairment resulting from SD by conducting a systematic review and meta-analysis. This study comprehensively searched eight databases for randomized controlled trials (RCTs) that examine the effects of acupuncture on SD-induced cognitive impairment. Primary outcomes were assessed using the Morris Water Maze (MWM), including measures of escape latency and time spent in the target quadrant. Secondary outcomes focused on molecular markers such as brain-derived neurotrophic factor (BDNF), tropomyosin receptor kinase B (TrkB), and indicators of oxidative stress. The risk of bias was evaluated using the SYRCLE tool, and data were analyzed using R software. Standardized mean differences (MD) and 95% confidence intervals (CIs) were calculated. Eight RCTs involving 222 rodents were analyzed. The findings indicate that acupuncture significantly improves cognitive performance in SD models, evidenced by increased platform crossings [MD = 1.67, 95% CI (1.42, 1.91)] and extended time in the target quadrant [MD = 8.54, 95% CI (6.35, 10.73)], along with reduced escape latency [MD = -8.33, 95% CI (-11.68, -4.99)]. Electroacupuncture (EA) was found to regulate the expression of BDNF and its receptor, TrkB, and to decrease oxidative stress markers such as malondialdehyde (MDA) while enhancing antioxidant activities, including those of superoxide dismutase (SOD). Manual acupuncture (MA) influenced apoptosis markers by decreasing Bax and increasing Bcl-2 expression. Despite these positive findings, the studies exhibited heterogeneity in intervention methods and variability in acupuncture techniques. This study preliminarily confirms that acupuncture, specifically electroacupuncture, and manual acupuncture, can effectively alleviate cognitive impairment caused by sleep deprivation. The benefits are observed through modulation of BDNF-TrkB signaling, reduction in oxidative stress, and regulation of apoptosis. Although the current evidence is derived from animal studies, it suggests potential applications in human clinical trials to explore the viability of acupuncture for treating cognitive impairment related to SD. CRD42024627285, https://www.crd.york.ac.uk/PROSPERO/.